Comparative Genomic Data Provide New Insight on the Evolution of Pathogenicity in Sporothrix Species - Huang, Mengya; Ma, Ziying; Zhou, Xun (Frontiers in Microbiology, 2020)
Sporothrix species are commonly isolated from environmental and clinical samples. As common causes of zoonotic mycosis, Sporothrix species may result in localized or disseminated infections, posing considerable threat to animal and human health. However, the pathogenic profiles of different Sporothrix species varied, in virulence, geographic location and host ranges, which have yet to be explored. Analysing the genomes of Sporothrix species are useful for understanding their pathogenicity. In this study, we analysed the whole genome of twelve Sporothrix species and six S. globosa isolates from different clinical samples in China. By combining comparative analyses with Kyoto Encyclopaedia of Genes and Genomes (KEGG), Carbohydrate-Active enZymes (CAZy), antiSMASH, and Pfam annotations, Sporothrix species showed exuberant primary and secondary metabolism processes. The genome sizes of four main clinical species, i.e. S. brasiliensis, S. schenckii, S. globosa and S. luriei were significantly smaller than other environmental and clinical Sporothrix species, and the contracted genes included mostly CAZymes and peptidases genes which were usually associated with the decay of plants. These results could partly explain the evolution of habitat shift of Sporothrix species from a saprobic life in plant materials to a pathogenic life in mammals. Gene clusters of melanin and clavaric acid were identified in this study, which improved our understanding on their pathogenicity and possible antitumor effects. Moreover, our analyses revealed no significant genomic variations among different clinical isolates of S. globosa from different regions in China.